Exploring Habits of Mind Associated With Incremental Learning Theory To Explain Actions of Teachers Integrating Environmental Education - Lane, Jennie F.; Franzen, Rebecca L.; Altan, Servet (Routledge Journals, Taylor & Francis Ltd, 2024)
This study was launched after re-analyzing teacher narratives from an earlier study; the narratives were reflections on environmental education practices. The analysis involved using a framework that relates Habits of Mind to educational theories. An unsurprising outcome was finding Habits of Mind associated with mindfulness and constructivism. An unanticipated finding was to learn how incremental learning theory explains why teachers strive to include environmental education in their lessons. Although there has been environmental research related to growth and fixed mindsets, more studies in environmental education are needed to explore how incremental learning theory plays a role in the decisions and actions of exemplary environmental educators. Therefore, to begin this exploration, a new study was conducted using the framework to analyze interviews with ten currently practicing teachers. The findings give insights into the following Habits of Mind associated with incremental beliefs: wonderment and awe, continuous learning, striving for accuracy, risk-taking, and persistence.
Keywords: Environmental educators; Growth mindset; Incremental learning theory; Habits of mind; Sdg 4: quality education